A Case Study Demonstrating Reduction of Aggressive Client Behaviors Using the Neuro-Occupation Model: Addressing Professional Burnout through Nonlinear Thinking. (3rd April 2017) - Piven, Emily F.; Derakhshanrad, Seyed Alireza
ABSTRACT: This single case study suggests that mental health practitioners adopt nonlinear modes of thinking within the neuro-occupation model to avoid professional burnout. Accordingly, the elimination of severely aggressive behavior of an institutionalized client was reviewed following an intervention using the model. Provided with new opportunities, the client self-extinguished aggressive interactions, reinstated social behaviors, and expanded occupations. Accepting clients as their own change agents limits our role to facilitators and reframes service delivery in mental health, which argues for comparison studies that measure reduced burnout in occupational therapists using the model.